Dietary habits of fishing cats in a human-dominated wetland in Coastal Thailand - THAKSIN WONGSON; SUPAWAT KHAEWPHAKDEE; WIROON MONGKONSIN; LAUREL E. K. SERIEYS; WAI-MING WONG; MARNOCH YINDEE; RATTAPAN PATTANARANGSAN; WARONG SUKSAVATE; PONGSATORN PROMKUNTOD; CHAIWAT KLAKHAENG; RONGLARP SUKMASUANG (Society for Indonesian Biodiversity, 2024)
Abstract. Wongson T, Khaewphakdee S, Mongkonsin W, Serieys LEK, Wong W-M, Yindee M, Pattanarangsan R, Suksavate W, Promkuntod P, Klakhaeng C, Sukmasuang R. 2024. Dietary habits of fishing cats in a human-dominated wetland in Coastal Thailand. Biodiversitas 25: 2788-2797. Fishing cats, intimately connected to wetland habitats, face an escalating threat from human activities and environmental change. With its significant findings, this study offers a comprehensive insight into the dietary habits of fishing cats in a human-dominated wetland in coastal Thailand. By examining the scats of 192 fishing cats (Prionailurus viverrinus Bennett 1833) and the remains of 328 prey items, we detailed the fishing cat's diet and assessed its seasonality. Consequently, we identified 16 prey species consumed by fishing cats during the study period. The primary prey was fish, followed by rodents, birds, Indo-Chinese rat snakes (Ptyas korros (Hermann Schlegel 1837)), insects, crabs, and snails. The most crucial prey was the climbing perch (Anabas testudineus Bloch 1792) (n=69), followed by bandicoot rats (Bandicota indica Bechstein, 1800) (n=54), domestic chicken (Gallus gallus Linnaeus 1758) (n=48), and snakehead murrel (Channa striata Bloch 1793) (n=38). The niche breadth index indicated the highest specialization during the summer, while the dietary diversity index was 0.44, 0.52, and 0.38 during the summer, rainy, and winter seasons, respectively. Seasonal variations in dietary composition were not statistically significant. The niche overlap index was 0.95 between the summer and the rainy season, 0.91 between the rainy season and winter, and 0.87 between the summer and winter. These findings, with their direct implications for the conservation of fishing cats, highlight the urgent need for effective land-use management in species preservation.